The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1097/brs.0000000000004682
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery Before Spine Surgery is Associated with Fewer Post-Surgical Complications

Abstract: Study Design. Systematic review and meta-analysis. Objective. To perform a systematic review and meta-analysis investigating the rate of adverse events after spine surgery in patients who underwent bariatric surgery (BS). Summary of Background Data. Obesity is an established risk factor for postoperative complications after spine surgery. BS has been associated with improvements in health in patients with severe obesity. However, it is not known whether undergoing BS before spine surgery is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Multiple studies have also shown that bariatric surgery can reduce the risk for medical complications after spine surgery. [21][22][23][24] Jain et al 21 used a retrospective cohort study of 590 patients who had undergone bariatric surgery before lumbar fusion to show this difference, but noted these patients still had increased risk for complications, infections, and reoperation when compared with nonobese patients. Recently, Gupta et al 23 redemonstrated this reduced risk of postoperative medical complications, but noted no reduction in surgical complications or 30-day readmission rates in their meta-analysis.…”
Section: Preoperative Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have also shown that bariatric surgery can reduce the risk for medical complications after spine surgery. [21][22][23][24] Jain et al 21 used a retrospective cohort study of 590 patients who had undergone bariatric surgery before lumbar fusion to show this difference, but noted these patients still had increased risk for complications, infections, and reoperation when compared with nonobese patients. Recently, Gupta et al 23 redemonstrated this reduced risk of postoperative medical complications, but noted no reduction in surgical complications or 30-day readmission rates in their meta-analysis.…”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…[21][22][23][24] Jain et al 21 used a retrospective cohort study of 590 patients who had undergone bariatric surgery before lumbar fusion to show this difference, but noted these patients still had increased risk for complications, infections, and reoperation when compared with nonobese patients. Recently, Gupta et al 23 redemonstrated this reduced risk of postoperative medical complications, but noted no reduction in surgical complications or 30-day readmission rates in their meta-analysis. Therefore, it is clear that although bariatric surgery shows promising benefits, it does not entirely mitigate the risk of postoperative complications in these patients.…”
Section: Preoperative Considerationsmentioning
confidence: 99%
See 1 more Smart Citation